Conceptual Study of Selfie As a New Tool for Brand Marketing - Endang Hariningsih; Budhi Haryanto (International Journal of Marketing & Human Resource Research, 2022)
This paper aims to propose a proposition of selfie effectiveness from influencers that impact the attitude and buying intentions. The method is to review of several articles reveals the phenomenon of selfie marketing and the science of exercise to develop a proposition about the effectiveness of selfies concerning forming positive attitudes and purchasing intentions of a brand. The study produced a conceptual framework based on Stimuli-Organism-Response (SOR) as the basis for the development of propositions that explain the relationship between selfie charm and self-congruence, attitudes toward influencers, and attitudes toward brands and purchasing intentions with social interaction as moderation variables of the relationship between those variables. This paper describes selfies taken by non-celebrities as influencers. The implication of this study is an alternative model that conceptualizes selfie charm and social interaction as two variables that influence the process of forming a brand's buying attitudes and intentions, which marketers need to consider in creating marketing strategies. The phenomenon of selfies that occur today has given rise to a new stimulus, namely the charm of selfies and netizen comments that affect consumer activity in the purchase of a brand.